2022
DOI: 10.1001/jamanetworkopen.2022.48060
|View full text |Cite
|
Sign up to set email alerts
|

Association of Developmental Language Disorder With Comorbid Developmental Conditions Using Algorithmic Phenotyping

Abstract: ImportanceDevelopmental language disorder (DLD) is a common (with up to 7% prevalence) yet underdiagnosed childhood disorder whose underlying biological profile and comorbidities are not fully understood, especially at the population level.ObjectiveTo identify clinically relevant conditions that co-occur with DLD at the population level.Design, Setting, and ParticipantsThis case-control study used an electronic health record (EHR)–based population-level approach to compare the prevalence of comorbid health phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…In this context, some studies have found the coexistence of these conditions had an additional effect on the educational results of children [23,24]. In fact, children with DLD may have attention deficits that are not significant enough to warrant a diagnosis of ADHD, but still affect their learning in the classroom [25].…”
Section: Comorbiditymentioning
confidence: 99%
“…In this context, some studies have found the coexistence of these conditions had an additional effect on the educational results of children [23,24]. In fact, children with DLD may have attention deficits that are not significant enough to warrant a diagnosis of ADHD, but still affect their learning in the classroom [25].…”
Section: Comorbiditymentioning
confidence: 99%
“…Extant research has primarily focused on childhood developmental disorders, including autism spectrum disorder and attention-deficit/ hyperactivity disorder, but not as much on large-scale studies of speech and language. 22 An Automated Phenotyping Tool for Identifying Developmental Language Disorder algorithm has been developed and used in singlecenter studies. 21 Given the lack of data about the trajectory of speech and language disorders in young children and the need for more data in this area, a rigorous approach to gathering and documenting speech and language data at the time of initial DBP evaluation and diagnosis should be a priority for our field.…”
Section: Current Documentation Practicesmentioning
confidence: 99%
“…A clear understanding of the influence of medication on language outcomes is of critical relevance to speech pathologists working with child and adult populations given the co-occurrence of ADHD with conditions such as dyslexia, developmental language disorder, and autism, as well as the growing recognition of the subclinical language differences associated with ADHD (Germanò et al, 2010;Nitin et al, 2022). Speech pathologists are likely to work as part of multidisciplinary teams, so knowing how medication impacts language skills allows for greater treatment coordination with other health professionals, such as psychiatrists or general practitioners prescribing medication.…”
Section: Introductionmentioning
confidence: 99%